Displacement Earth's surface modeling with GIS technologies use in the mining of mineral deposits - Kuchin, O. S.; Nazarenko, V. O.; Bruy, H. V.; Balafin, I.; Кучин, О. С.; Назаренко, В. О.; Бруй, Г. В.; Балафін, І. (IOP Publishing, 2025)
The results of geodetic (mine surveying) observations and the results of threedimensional modeling of the earth's surface displacements at the observation station, laid over the 124th longwall of the Blagodatnaya Mine in the Western Donbass (Ukraine), are presented. To determine the displacements and deformations, the ground benchmarks of the profile lines were coordinated using a GNSS receiver and an electronic total station with an accuracy of their spatial position of 4-5 mm. Processing of the results of observations was carried out using the software product SAMARa (Automation System for Mine Surveying). Spatial 3D models of the displacement of points on the earth's surface in the zone of influence of mining operations have been built. With their help, it is possible to solve problems of establishing the actual values of displacements and deformations of the earth's surface in undermined territories. A 3D model of displacements of points on the earth's surface, predicted according to the methodology of the current State Standards of Ukraine, will make it possible to assess the impact of underground mining on the ecological situation of the undermining area and the safety of civil and industrial structures in the hazardous zone.